Environmental Influence Social Governance , Leverage , and Managerial Ability Towards Tax Avoidance - Fifi Arianti; Aisyaturrahmi Aisyaturrahmi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to get empirical evidence on the effect of Environmental Social Governance (ESG), leverage , and managerial abilities on tax avoidance in manufacturing industry companies listed on the Indonesian Stock Exchange for the 2021-2023 period with a total of 129 observations . The research method uses a quantitative approach with panel data regression and secondary data from annual reports and company sustainability reports . Data analysis was carried out using Stata 17 software . The results of the study show that ESG and leverage have a positive effect on tax avoidance , while managerial ability has no effect on tax avoidance . This finding indicates that ESG disclosure is still used as a legitimacy tools without being accompanied by compliant tax practices . Therefore , companies are advised to ensure that reported sustainability practice reflect responsible tax compliance